Probiotic therapy in patients with irritable bowel syndrome: does it have a real role? - Iman Mohamed Fawzy; Eman Mohamed ElGindy; Omar Abdel-Samie; Heba Aly (SpringerOpen, 2021)
Abstract Background Irritable bowel syndrome (IBS) is one of the most prevalent functional gastrointestinal disorders (FGIDs). There is good evidence that microbiota plays a predominant role in the IBS pathophysiology. The aim of the study is to evaluate the role of probiotics in improvement of IBS symptoms via IBS-symptom severity scale (IBS-SSS Arabic version) and improvement of quality of life via irritable bowel syndrome-quality of life survey (IBS-QOL). Results This double-armed comparative trial was conducted on IBS patients, who fulfill ROME IV criteria and the IBS diagnostic questionnaire between August and December 2019. Ninety patients were followed up for 4 weeks from the first visit. The first group was prescribed probiotics (10 billion colony of Lactobacillus delbruekii and Lactobacillus fermentum) and itopride hcl 50 mg three times daily, while the second group received only itopride hcl 50 mg by the same dose for 4 weeks. There was a highly significant improvement in the IBS-SSS score in group 1 after 4 weeks of treatment than in group 2 (137.56±67.53 vs 258.44±34.18) (p=0.001). Also, there was a highly significant improvement in the overall QOL terms in group 1 in comparison with baseline QOL score [with overall mean score (60.64±7.77) at baseline vs (81.54±7.87) at 4 weeks (p value <0.001)]. Conclusion Probiotics are useful for the improvement of IBS symptoms and quality of life of the studied patients. Larger multicenter studies are needed in the future.